Understanding Physicians’ Online-Offline Behavior Dynamics: An Empirical Study - Wang, Liuan; Yan, Lu (Lucy); Zhou, Tongxin; Guo, Xitong; Heim, Gregory R. (Information Systems Research, 2020)
Online healthcare platforms allow physicians and patients to communicate in a timely manner. Yet little is known about how physicians’ online and offline activities affect each other and, consequently, the healthcare system. We collected data from both online and offline channels to study physicians’ online-offline behavior dynamics. We find that physicians’ online activities can lead to a higher service quantity in offline channels, whereas offline activities may reduce physicians’ online services because of resource constraints. We also find that the more offline patients that physicians serve, the more articles the physicians will likely share in online healthcare platforms. These findings are of great importance to practitioners and policy makers. Our work provides evidence that online healthcare platforms supplement offline services and thus lessen the concern that physicians’ participation in online healthcare platforms will negatively influence offline healthcare services. Our findings also indicate the need for the improvement of online-offline coordination and better system design.